2015
DOI: 10.2224/sbp.2015.43.7.1135
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Functioning and Mental Health Condition on the Child's Behavioral Problems

Abstract: We examined correlates of mental health conditions among family members and explored the effects of mothers' and fathers' mental health and family functioning on their child's behavioral problems. Participants were 119 couples in China, of whom the majority were parents in 1-child families. These parents reported their own anxiety and depression symptoms, behavioral problems of their child, and perceived family functioning. Results indicated that the mental health condition of the father, mother, and child we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…A mother's MH problems were also seen to exert more of an influence on child MH outcomes than a father's MH (e.g. Wang & Zhou ). This is possibly because mothers are frequently the primary caregivers and therefore exert more influence over the child's MH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A mother's MH problems were also seen to exert more of an influence on child MH outcomes than a father's MH (e.g. Wang & Zhou ). This is possibly because mothers are frequently the primary caregivers and therefore exert more influence over the child's MH.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies followed a cross‐sectional survey design (n = 21), all the studies were quantitative, and approximately one‐third were conducted in the USA (n = 14). The mean age of the total sample of children included was 10.8 years, and four studies did not report the mean age of the sample (Goldfeld & Hayes ; Piche et al ., ; Roustit et al ., ; Wang & Zhou ). Sample sizes ranged from 40 to 5,607 participants (Faust & Stewart ; Yen et al , ); and most studies (n = 23) reported a relatively equal gender representation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Wang &Zhou (2016) revealed that, the continuity of family connections and a secure emotional base is crucial for the positive development of young people and protective factors against a range of health risk behaviors. (27) .…”
Section: Discussionmentioning
confidence: 99%
“…КЉУЧНЕ РЕЧИ: партнерска афективна везаност; једнородитељство; ставови жена. УВОД РОДИТЕЉСТВО У скоро свим 9исци@линама које изучавају ро9иNељсNво (социоло:ија, @е9а:о:ија, ан9ра:о:ија), као најважнија каракNерисNика @оро9ице исNиче се њена важносN за емоционални и социјални развој 9еNеNа (Mirabile, 2014;Turney, Lee, & Mehta, 2013;Norona & Baker, 2014;Wang & Zhou, 2015). Неа9екваNан о9нос са ро9иNељима може 9овесNи 9о @роKлема у вршњачким :ру@ама: а:ресив-носN, 9е@ресивносN, @овлачење и слична сNања, као и оKлици @онашања 9еNеNа у великој мери @овезани су у@раво са неси:урним афекNивним о9носима ро9иNеља и 9еце (Coleman, 2003).…”
unclassified